2014
DOI: 10.1111/nyas.12322
|View full text |Cite
|
Sign up to set email alerts
|

Capacity building in the health sector to improve care for child nutrition and development

Abstract: The effectiveness of interventions promoting healthy child growth and development depends upon the capacity of the health system to deliver a high-quality intervention. However, few health workers are trained in providing integrated early child-development services. Building capacity entails not only training the frontline worker, but also mobilizing knowledge and support to promote early child development across the health system. In this paper, we present the paradigm shift required to build effective partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
(57 reference statements)
1
22
0
5
Order By: Relevance
“…This finding is highly consistent with what others have previously identified as a top priority of scaling up integrated ECD programs [21,22], lending further credibility to our results. Collectively, the 75 countries with more than 95% of the current burden of maternal and child mortality have an estimated median of 10.2 physicians, nurses and midwives per 10 000 people, and three–quarters are below the World Health Organization benchmark of 22.8 per 10 000 [1].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is highly consistent with what others have previously identified as a top priority of scaling up integrated ECD programs [21,22], lending further credibility to our results. Collectively, the 75 countries with more than 95% of the current burden of maternal and child mortality have an estimated median of 10.2 physicians, nurses and midwives per 10 000 people, and three–quarters are below the World Health Organization benchmark of 22.8 per 10 000 [1].…”
Section: Discussionsupporting
confidence: 93%
“…Systematic reviews of in-service nutrition training have found that it improves the nutrition counselling and child undernutrition management of health workers (66,67) . In-service nutrition training programmes existed in less than half of the countries in West Africa and continuing training efforts were mainly concentrated on staff at national and regional levels, leaving health staff at lower levels with inadequate capacities in nutrition.…”
Section: Workforce Preparationmentioning
confidence: 99%
“…8 Data were compiled from multiple sources, including monthly, quarterly, and annual project reports submitted by project teams to WHO and GAC, and reports after WHO site visits to each project. Training data included training content and methods, participant numbers, cadres, and level of health system where they were conducted.…”
Section: Methodsmentioning
confidence: 99%